An Analysis of Product Quality Control using The Six Sigma Method at Omah Produksi Tempe Rizky Jaya, Batu City - Novita Nurrry Chrisyani; Cakti Indra Gunawan; Yuni Setyawati (International Journal of Management and Business, 2026)
This study aims to analyze product quality control using the Six Sigma method at Omah Tempe Production Rizky Jaya MSME in Batu City. The main problem faced by this MSME is the high level of defective products such as mushy textured tempeh and moldy tempeh. The Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach is applied to identify the causes of defects, analyze the performance of the production process, and provide recommendations for improvement. The results showed an average sigma value of 3.30, indicating that the production process is still at a medium level and needs to be improved. The main factors causing defects are humans, raw materials, machines, work methods, and the environment. Recommendations for improvement include workforce training, improved sanitation, and standardization of production procedures.